Polypyrrole film based flexible supercapacitor: mechanistic insight into influence of acid dopants on electrochemical performance. (10th October 2020) - Zhang, Miaomiao; Nautiyal, Amit; Du, Haishun; Li, Junhao; Liu, Zhongqi; Zhang, Xinyu; Wang, Ruigang
Abstract: The present study is aimed at providing a mechanistic insight into the influence of acid dopants on electrochemical performance of polypyrrole (PPy) film based flexible supercapacitor. PPy films were electrochemically deposited on carbon cloth using different kinds of acid dopants: hydrochloric acid (HCl), perchloric acid (HClO4 ), sulfuric acid (H2 SO4 ), p-toluenesulfonic acid (p-TSA), phosphoric acid (H3 PO4 ) and phytic acid (PA). Results show that both the size and type of dopants have a great influence on the doping level, mass ratio of counterions, accessibility of redox sites and the electrochemical performance of the PPy film electrodes. Among the obtained electrodes, PPy/HCl exhibits the highest specific capacitance of 960 F g −1 at 5 mV s −1, yet with inferior cycling stability. Interestingly, PPy/p-TSA shows the best cycling stability with more than 75% of capacitance retention after 2000 cycles, also with a relatively high specific capacitance (572 F g −1 at 5 mV s −1 ). Moreover, the PPy/p-TSA is used to fabricate a flexible all-solid-state supercapacitor device which exhibits a maximum energy density of 6.2 Wh kg −1 and a power density of 2.64 KW kg −1, respectively. Intriguingly, the assembled PPy/p-TSA devices exhibit excellent cycling stability with 88% capacitance retention after 6000 cycles. This fundamental study provides new prospects for developing PPy-based electrode materials for future flexible and wearable supercapacitors. Graphical abstract: Image, graphical abstract